Impact of Product Reviews and Online Information Search on Purchase Intention among Nepalese Online Consumers - Sejuwal, Narendra (NPRC Journal of Multidisciplinary Research, 2025)
Background: Indeed, the global rise of e-commerce has led to a situation where buyers need to make purchase decisions based on digital cues such as online reviews and information search. Whereas meta-analytic evidence confirms their strong influence on purchase intention, these contextual factors shaped by culture and market maturity, among other influences. In Nepal, a fast-growing e-commerce landscape creates peculiar dynamics in which consumers, notwithstanding challenges of trust and heterogeneity of platforms, rely on these informational sources. Nevertheless, integrated research that examines how product reviews and active information search interactively affect Nepalese consumer purchase intention remains scant. Objectives: The purpose of this study is to examine the influence of product reviews and online information search on the purchase intention of Nepalese online consumers and to find out gender-based differences in purchasing behavior within the Kathmandu Valley. Methods: The research design adapted was cross-sectional, descriptive, and exploratory. Quantitative data for the study were collected using a structured questionnaire among 384 active online consumers in Kathmandu Valley, selected by using a simple random sampling method. The instrument had acceptable reliability (Cronbach’s α = .751). Data analysis consisted of descriptive statistics and independent samples t-test that outlined the gender differences in purchase intention. Findings: Descriptive results showed that Nepalese online consumers rely heavily on comparisons and reviews, as 77.1% read reviews before purchase. Social influence from family and friends was moderately relevant, while recommendations from sellers were viewed skeptically. One key finding is that there is a statistically significant gender difference in purchase intention, t=3.58, p=.000, with female consumers reporting stronger purchase intention, Mean=2.25, than males, Mean=2.49, which suggests that females are a more decisive and homogeneous high-intent segment. Conclusions: The study concludes that online reviews and information search are pivotal for Nepalese consumers and that gender significantly moderates purchase intention. However, female consumers manifest stronger and more consistent intent to buy online; this would indicate that they are particularly responsive to informational and social proof cues. Practice: Nepalese e-commerce platforms and marketers should employ gender-responsive strategies. Emphasize detailed product reviews, user-generated content, and social proof to female consumers, while messaging to the male audience should focus on functional benefits price, efficiency, and convenience.